Preparation method of anode foil and aluminum electrolytic capacitor
By coating the aluminum slurry and protective film layer on the surface of the aluminum foil substrate and rolling and sintering, the problems of insufficient bending resistance and surface defects of the existing anode foil are solved, and high-quality anode foil preparation is achieved.
Patent Information
- Application Number
- CN202510194656.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The anode foil of existing aluminum electrolytic capacitors has shortcomings in its bending resistance, and the surface is prone to scratching and adhesion problems, affecting the quality and performance of the product.
Using a new anode foil preparation method, an aluminum foil blank is formed by coating an aluminum slurry on the surface of the aluminum foil substrate and drying it, and then a protective film layer is coated on the surface and rolled, and finally a sintering process is performed to form a sintered foil. This method improves the bending resistance of the anode foil and avoids surface defects by adding ceramic powder and using large diameter rolls.
The bending resistance of the anode foil is improved, the surface defects are reduced, and the surface is smooth and complete, thereby improving the overall performance of the aluminum electrolytic capacitor.
Smart Images

Figure CN119673672A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of capacitors, and in particular to a method for preparing an anode foil and an aluminum electrolytic capacitor. Background Art
[0002] Aluminum electrolytic capacitors have the advantages of small size, low cost, and large capacity, and are widely used in the electronics industry. With the development of technology, higher requirements are placed on the overall performance and size of devices used in automotive electronics, household appliances, and industrial control. The performance and quality of aluminum electrolytic capacitors also need to match the overall performance of the devices, prompting aluminum electrolytic capacitors to further develop in the direction of high capacity, miniaturization, and greening. The requirements for the bending resistance of the anode foil of aluminum electrolytic capacitors are also getting higher and higher.
[0003] At present, the aluminum foil can be passed through an inclined roller set in a conveying trough or a roller with a ball that can rotate around its own ball center on the circumferential surface to produce irregular multi-directional cracks on the surface of the aluminum foil, thereby improving the bending resistance of the anode foil in the horizontal and vertical directions. However, this treatment method is prone to problems such as scratching and powdering of the foil surface and wrinkling of the foil, which in turn causes the foil to stick when the aluminum foil is rolled and sintered, and it is impossible to produce an anode foil with a smooth surface and good bending resistance.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In view of this, a method for preparing an anode foil and an aluminum electrolytic capacitor are provided, wherein the preparation method can improve the bending resistance of the anode foil, reduce defects on the surface of the anode foil, and ensure the integrity and flatness of the surface of the anode foil.
[0006] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.
[0007] According to one aspect of the present disclosure, a method for preparing an anode foil is provided, the method comprising: Step S1: preparing an aluminum-containing slurry, wherein the aluminum-containing slurry comprises a mixed solution and a solid aluminum-containing powder, wherein the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder comprises aluminum powder and ceramic powder; Step S2: providing an aluminum foil substrate, coating the aluminum-containing slurry on the surface of the aluminum foil substrate, and performing a drying process to form an aluminum foil blank; Step S3: coating a thin film solution on the surface of the aluminum foil blank, and performing a drying process to form a protective film layer on the surface of the aluminum foil blank; Step S4: using a rolling mill to perform a rolling process on the aluminum foil blank having the protective film layer in a skew rolling manner to obtain an initial anode foil; Step S5: sintering the initial anode foil to remove the protective film layer to form a sintered foil.
[0008] In an exemplary embodiment of the present disclosure, the rolling mill is one of a two-roll rolling mill, a three-roll rolling mill or a four-roll rolling mill, the rolling mill has a roller pressure of 5 μm to 15 μm, and the roller diameter is 65 mm to 600 mm. In step S4, the aluminum foil blank having the protective film layer is rolled by the rolling mill in a skew rolling manner to obtain an initial anode foil. The method includes: The aluminum foil blank having the protective film layer is subjected to a first rolling process, wherein the first rolling process is to repeatedly roll the aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 20° to 70° with the length direction of the aluminum foil blank; The aluminum foil blank with the protective film layer is then subjected to a second rolling treatment, wherein the second rolling treatment is to repeatedly roll the aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 110° to 160° with the length direction of the aluminum foil blank.
[0009] In an exemplary embodiment of the present disclosure, the film solution is an aqueous solution prepared by one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; in step S3, the film solution is coated on the surface of the aluminum foil blank, and the method includes: The aluminum foil blank is coated with the thin film solution on both sides by using a doctor blade coating or screen printing method; the thickness of the protective film layer on each side of the aluminum foil blank is the same, and the thickness of the protective film layer on each side of the aluminum foil blank is 5μm~30μm.
[0010] In an exemplary embodiment of the present disclosure, the mass fraction of the ceramic powder to the solid aluminum-containing powder is 1% to 10%; the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80 to 250).
[0011] In an exemplary embodiment of the present disclosure, the ceramic powder is one or more of aluminum oxide, titanium dioxide, barium titanate, and strontium titanate; and the particle size of the ceramic powder is 0.5 μm to 10 μm.
[0012] In an exemplary embodiment of the present disclosure, the mass ratio of the solvent, the binder, and the additive in the mixed solution is 100:(3-10):(0.5-10); The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or both of terpineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol; The binder is one or two of ethyl cellulose and polyvinyl butyral; The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent.
[0013] In an exemplary embodiment of the present disclosure, the thickness of the aluminum foil substrate is 20 μm to 60 μm, and the aluminum foil substrate has an upper surface and a lower surface arranged opposite to each other. In step S2, the aluminum foil blank is formed, and the method includes: The aluminum foil substrate is double-sided coated with the aluminum-containing slurry to form aluminum slurry film layers with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; The aluminum foil substrate with the aluminum paste film layer is dried at a drying temperature of 90° C. to 200° C., and the thickness of the aluminum paste film layer after drying is 50 μm to 60 μm.
[0014] In an exemplary embodiment of the present disclosure, in step S5, the sintering process includes: In an air atmosphere, heating the initial anode foil from room temperature to 300° C. to 500° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 1 h to 8 h; In a nitrogen, argon or vacuum atmosphere, the initial anode foil is continuously heated to 610° C. to 650° C. at a heating rate of 0.1° C. / min to 20° C. / min, and kept at this temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
[0015] In an exemplary embodiment of the present disclosure, after step S5, the method further includes: The sintered foil is subjected to a water boiling treatment to form an intermediate anode foil, wherein the water boiling treatment comprises boiling the sintered foil in deionized water at 100° C. for 5 to 15 minutes; The intermediate anode foil is subjected to a chemical formation treatment to form an oxide layer on the intermediate anode foil to obtain a target anode foil, wherein a chemical formation voltage of the chemical formation treatment is 200V to 700V.
[0016] According to another aspect of the present disclosure, an aluminum electrolytic capacitor is provided. The aluminum electrolytic capacitor includes an anode foil manufactured by the above-mentioned preparation method.
[0017] The present disclosure provides a method for preparing an anode foil, wherein ceramic powder is added to an aluminum-containing slurry, the aluminum-containing slurry is coated on the surface of an aluminum foil substrate, and dried to obtain an aluminum foil blank, and then a protective film layer is coated on the surface of the aluminum foil blank, and the aluminum foil blank is rolled by a rolling mill in a skew rolling manner, and sintered to obtain a sintered foil. The surface of the sintered foil obtained by the preparation method has irregular multi-directional cracks, which can improve the subsequent anti-bending performance of the anode foil; in addition, the preparation method can solve the problem of scratching and powdering of the surface of the anode foil by first coating the protective film layer on the surface of the aluminum foil blank and then skew rolling by a rolling mill, and the protective film layer can form a gap between adjacent aluminum foil blanks, and in the subsequent sintering process, the adhesion between the aluminum foil blanks is avoided; in addition, the roller used in the preparation method is a large-diameter roller (diameter of 65mm-300mm), and the roller has better rigidity, which can effectively improve the problem of foil wrinkles caused by roller bending, improve the production quality of the anode foil, and produce an anode foil with a smooth surface and good anti-bending performance by the preparation method.
[0018] The aluminum electrolytic capacitor provided by the present disclosure includes an anode foil prepared by the above method. The capacitor has good mechanical properties and good overall device performance.
[0019] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0021] Figure 1 The present invention is a flowchart of a method for preparing an anode foil in an exemplary embodiment of the present invention.
[0022] Figure 2 This is an optical microscope image of the anode foil prepared in Comparative Example 1.
[0023] Figure 3 This is an optical microscope image of the anode foil prepared in Comparative Example 2.
[0024] Figure 4 This is an optical microscope image of the anode foil prepared in Example 1 provided in the present disclosure. DETAILED DESCRIPTION
[0025] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.
[0026] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.
[0027] In the related art, in order to improve the bending resistance of the electrode foil, cracks can be processed on the surface of the foil by using an inclined roller (with a diameter of 6mm to 20mm). The foil is passed around the conveying roller and the roller. The conveying roller is used to transmit the foil forward. The foil passes around the roller at an angle. Since the bending contact surface is at an angle to the width direction of the foil, corresponding cracks are generated when the foil is bent by the roller. Multiple groups of rollers can be set to process multiple cracks at the same time; a number of balls (with a diameter of 2mm to 4mm) that can rotate around their own spherical centers can also be provided on the circumferential surface of the roller (with a diameter of 8mm to 12mm). The balls are in contact with the electrode foil, and the foil surface of the electrode foil is made to roll relative to the balls that can rotate around their own spherical centers in multiple directions and to interact with each other under the winding tension, thereby forming multi-directional cracks on the foil surface of the electrode foil.
[0028] However, the surface of the electrode foil prepared by the above two methods is prone to scratching and powdering, and the flatness and integrity of the electrode foil surface cannot be guaranteed, which leads to easy adhesion of the foil when the aluminum foil is rolled and sintered; in addition, the existing technology uses small-diameter rollers (20 mm and below), which have poor rigidity and are easy to bend during continuous foil processing, which easily leads to foil wrinkles, making it impossible to produce anode foil with a smooth surface and good anti-bending performance.
[0029] Based on this, the present disclosure provides a method for preparing an anode foil, such as Figure 1 As shown, the preparation method includes: step S1 to step S5.
[0030] Wherein, step S1: preparing aluminum-containing slurry, the aluminum-containing slurry includes a mixed solution and solid aluminum-containing powder, the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder includes aluminum powder and ceramic powder; Step S2: providing an aluminum foil substrate, coating an aluminum-containing slurry on the surface of the aluminum foil substrate, and performing a drying process to form an aluminum foil blank; Step S3: coating the thin film solution on the surface of the aluminum foil blank, and performing a drying process to form a protective film layer on the surface of the aluminum foil blank; Step S4: using a rolling mill to roll the aluminum foil blank with the protective film layer in a skew rolling manner to obtain an initial anode foil; Step S5: Sintering the initial anode foil to remove the protective film layer to form a sintered foil.
[0031] The present disclosure provides a method for preparing an anode foil, which includes adding ceramic powder to an aluminum-containing slurry, coating the aluminum-containing slurry on the surface of an aluminum foil substrate, drying to obtain an aluminum foil blank, and then coating the surface of the aluminum foil blank with a protective film layer, rolling the aluminum foil blank with a rolling mill by oblique rolling, and sintering to obtain a sintered foil. The sintered foil obtained by the preparation method has irregular multi-directional cracks on the surface and inside, which can improve the subsequent anti-bending performance of the anode foil; in addition, the preparation method can solve the problem of scratching, powdering and wrinkling of the surface of the anode foil by first coating the protective film layer on the surface of the aluminum foil blank and then oblique rolling with a rolling mill, and the protective film layer can form a gap between adjacent aluminum foil blanks, and in the subsequent sintering process, avoid adhesion between aluminum foil blanks, improve the production quality of the anode foil, and the preparation method can produce an anode foil with a smooth surface and good anti-bending performance.
[0032] The following will describe in detail the steps of the method for preparing the anode foil provided in the embodiment of the present disclosure: In the embodiment provided in the present disclosure, in step S1, an aluminum-containing slurry is prepared, and the aluminum-containing slurry includes a mixed solution and a solid aluminum-containing powder, the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder includes aluminum powder and ceramic powder.
[0033] Among them, the aluminum-containing slurry includes a mixed solution prepared by mixing a solvent, a binder and an additive. The mass ratio of the solvent, the binder and the additive in the mixed solution is 100:(3~10):(0.5~10). For example, the mass ratio of the three can be 100:3:0.5, 100:3:10, 100:10:0.5 or 100:10:10, etc. The mass ratio between the components in the mixed solution can be selected or adaptively adjusted according to the specific type and function of the component.
[0034] The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or two of pineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol. The binder is one or two of ethyl cellulose and polyvinyl butyral. The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent. By controlling the type and mass ratio of each component in the aluminum-containing slurry, the aluminum-containing slurry can have the characteristics of low evaporation rate at room temperature, easy storage, and moderate viscosity. The solvent is easy to volatilize during the drying process, the aluminum-containing slurry has good leveling properties, and there is no or little residue of the binder and additives during the heat treatment process.
[0035] Among them, the aluminum-containing slurry includes solid aluminum-containing powder, and the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80~250). For example, the mass ratio between the two can be 100:80, 100:100, 100:120, 100:140, 100:160, 100:180, 100:200, 100:220, 100:240 or 100:250, etc. The mass ratio between the mixed solution and the solid aluminum-containing powder is within the above range, which can improve the subsequent formation quality of the aluminum foil blank.
[0036] The solid aluminum-containing powder includes aluminum powder, the aluminum particles in the aluminum powder may be spherical or ellipsoidal, and the particle size of the aluminum powder is 0.5 μm (micrometer) to 5 μm, for example, the particle size of the aluminum powder may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc. In the process of preparing the aluminum powder, there may be a variety of aluminum powders of different particle sizes in the solid aluminum-containing powder, and in some exemplary embodiments, the particle sizes of the aluminum powders in the solid aluminum-containing powder may be the same or substantially the same. The mass purity of the aluminum powder is not less than 99.95%, for example, the mass purity of the aluminum powder may be 99.95%, 99.96%, 99.97%, 99.98% or 99.99%, etc.
[0037] The solid aluminum-containing powder includes ceramic powder, and the mass fraction of the ceramic powder in the solid aluminum-containing powder is 1% to 10%. For example, the mass fraction of the ceramic powder in the solid aluminum-containing powder may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The ceramic powder may be one or more of aluminum oxide, titanium dioxide, barium titanate, and strontium titanate. The particle size of the ceramic powder may be 0.5 μm to 10 μm. For example, the particle size may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. In the process of preparing aluminum powder, there may be a variety of ceramic powders of different particle sizes in the solid aluminum-containing powder. In some exemplary embodiments, the particle sizes of the ceramic powders in the solid aluminum-containing powder may be the same or substantially the same. By adding ceramic powder to solid aluminum-containing powder, the internal stress in the subsequent sintering process can be increased, so that irregular multi-directional cracks are formed inside the sintered foil. The high temperature resistance and chemical stability of the subsequently formed anode foil can also be improved, thereby increasing the service life of the anode foil.
[0038] In the embodiment provided in the present disclosure, in step S2, an aluminum foil substrate is provided, an aluminum-containing slurry is coated on the surface of the aluminum foil substrate, and a drying treatment is performed to form an aluminum foil blank.
[0039] The thickness of the aluminum foil substrate is 20 μm to 60 μm, for example, the thickness of the aluminum foil substrate may be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm, etc. The aluminum foil substrate has an upper surface and a lower surface that are relatively arranged. Since there may be subsequent differences between the parts of the aluminum foil substrate, the thickness of the aluminum foil substrate may refer to one of the maximum distance, the minimum distance or the average distance between the upper surface and the lower surface. In the present disclosure, the thickness of the aluminum foil substrate is taken as the average distance between the upper surface and the lower surface for explanation.
[0040] In some embodiments, in step S2, an aluminum foil blank is formed, including: using an aluminum-containing slurry to double-side coat an aluminum foil substrate to form an aluminum slurry film layer with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; drying the aluminum foil substrate with the aluminum slurry film layer at a drying temperature of 90°C to 200°C.
[0041] Among them, the double-sided coating of the aluminum foil substrate can be carried out by a coating method such as doctor blade coating and screen printing, and an aluminum paste film layer of the same thickness is formed on the upper surface and the lower surface of the aluminum foil substrate. The thickness of the aluminum paste film layer after drying is 50μm~60μm, for example, it can be 50μm, 52μm, 54μm, 56μm, 58μm or 60μm, etc. By controlling the thickness of the aluminum foil substrate and the aluminum paste film layer, a porous layer of appropriate thickness is formed on both sides of the aluminum foil blank, thereby improving the ductility of the aluminum foil blank in the subsequent rolling process.
[0042] It should be noted that the same thickness of the aluminum paste film layer formed on the upper surface and the lower surface of the aluminum foil substrate means that the thickness of the two is exactly the same or approximately the same. Due to process errors, the difference in thickness between the two is within 1 μm, and the thickness of the two can be considered to be the same.
[0043] After the aluminum film layer is formed on the surface of the aluminum foil substrate, the aluminum foil substrate is dried, wherein the drying temperature can be 90°C to 200°C, for example, the drying temperature can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc. The specific drying temperature can be adaptively adjusted according to the thickness of the aluminum film layer. For example, when the thickness of the aluminum film layer is thick, the drying temperature can be appropriately increased to shorten the drying time and improve the efficiency. The preparation method can control the drying temperature so that the slurry has good leveling during the drying process and the solvent evaporates more thoroughly.
[0044] In the embodiment provided in the present disclosure, in step S3, a thin film solution is coated on the surface of the aluminum foil blank, and a drying treatment is performed to form a protective film layer on the surface of the aluminum foil blank.
[0045] The film solution is an aqueous solution prepared from one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone.
[0046] A thin film solution is coated on the surface of an aluminum foil blank. The method includes: using a form of doctor blade coating or screen printing to coat the aluminum foil blank with a thin film solution on both sides; the thickness of the protective film layer on each side of the aluminum foil blank is the same. The thickness of the protective film layer on each side of the aluminum foil blank is 5μm~30μm, for example, the thickness of the protective film layer can be 5μm, 10μm, 15μm, 20μm, 25μm or 30μm. The same thickness of the protective film layer on each side of the aluminum foil blank means that the thickness of the two protective film layers is exactly the same or approximately the same. Due to process errors, the difference in thickness of the two protective film layers is within the range of 1μm, and the thickness of the two can be considered to be the same. This method controls the composition of the thin film solution and the thickness of the protective film layer, so that the protective film layer is not easy to fall off during the subsequent rolling process, so as to protect the aluminum slurry film layer from being scratched and powdered, and the protective film layer is easier to remove in the subsequent sintering process, and will not have an adverse effect on the overall structure of the anode foil.
[0047] In the embodiment provided in the present disclosure, in step S4, the aluminum foil blank having the protective film layer is subjected to a rolling process by a rolling mill in a skew rolling manner to obtain an initial anode foil.
[0048] The rolling mill may be one of a two-roller rolling mill, a three-roller rolling mill or a four-roller rolling mill. In order to improve the rolling quality of the aluminum foil blank by the rolling mill, the rolling mill roll pressure may be 5μm to 15μm, for example, the rolling mill roll pressure may be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, etc. In order to avoid the aluminum foil blank from powdering or scratching during the rolling process, the rolling mill roll diameter may be 65mm to 600mm, for example, the rolling mill roll diameter may be 65mm, 100mm, 150mm, 200mm, 250mm, 300mm, 350mm, 400mm, 450mm, 500mm, 550mm or 600mm, etc.
[0049] In some embodiments, the aluminum foil blank having the protective film layer is rolled by a rolling mill in a skew rolling manner to obtain an initial anode foil, and the method includes: The aluminum foil blank with a protective film layer is subjected to a first rolling treatment, in which the aluminum foil blank is repeatedly rolled 2 to 20 times when the axial direction of the roller is 20° to 70° with the length direction of the aluminum foil blank; the aluminum foil blank with a protective film layer is subjected to a second rolling treatment, in which the aluminum foil blank is repeatedly rolled 2 to 20 times when the axial direction of the roller is 110° to 160° with the length direction of the aluminum foil blank.
[0050] Among them, in the first rolling process, the axis direction of the roller and the length direction of the aluminum foil blank can be 20°~70°, for example, 20°, 30°, 40°, 50°, 60° or 70°, etc., and the number of rolling times can be 2 to 20 times; in the second rolling process, the axis direction of the roller and the length direction of the aluminum foil blank are 110°~160°, for example, 110°, 120°, 130°, 140°, 150° or 160°, etc., and the number of rolling times can be 2 to 20 times. In some exemplary embodiments, there is a correlation between the rolling angle of the rolling mill, the roller pressure, the roller diameter and the number of rolling times. When the roller diameter is large, one or more of the pressure, the rolling angle or the number of rolling times can be increased to improve the rolling efficiency and the rolling quality.
[0051] The method controls the rolling angle of the rolling mill, the amount of roller pressure of the rolling mill and the roller diameter of the rolling mill, so that the protective film layer on the surface of the aluminum foil blank is not easy to fall off during the rolling process, the aluminum slurry layer is not easy to be scratched and does not lose powder, and suitable internal stress can be generated around the ceramic powder in the aluminum slurry layer, so that the aluminum slurry layer produces irregular multi-directional cracks in the subsequent sintering process, thereby improving the bending resistance of the anode foil.
[0052] In the embodiment provided by the present disclosure, in step S5, the initial anode foil is sintered to remove the protective film layer to form a sintered foil.
[0053] The sintering treatment of the initial anode foil includes: heating the initial anode foil from room temperature to 300°C~500°C at a heating rate of 0.1°C / min~20°C / min in an air atmosphere, and keeping it warm for 1h~8h; continuing to heat the initial anode foil to 610°C~650°C at a heating rate of 0.1°C / min~20°C / min in a nitrogen, argon or vacuum atmosphere, and keeping it warm for 4h~12h; cooling with the furnace after the insulation is completed.
[0054] In the above embodiment, the initial anode foil is subjected to the first treatment, and the parameters of the first treatment are: in an air atmosphere, the first heating rate is 0.1°C / min~20°C / min, for example, the first heating rate may be 0.1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min, etc.; the initial anode foil is heated from room temperature to a first temperature, the room temperature is 20~25°C, the first temperature is 300°C~500°C, for example, the first temperature may be 300°C, 350°C, 400°C, 450°C or 500°C, etc.; the first insulation time is 1h~8h, for example, the first insulation time may be 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h, etc.
[0055] After the first treatment, the initial anode foil is subjected to a second treatment, and the parameters of the second treatment are: in a nitrogen, argon or vacuum atmosphere, a second heating rate is 0.1°C / min~20°C / min, for example, the second heating rate may be 0.1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min, etc.; the initial anode foil after the first treatment is heated from the first temperature to a second temperature of 610°C~650°C, for example, the second temperature may be 610°C, 620°C, 630°C, 640°C or 650°C, etc.; the second insulation time is 4h~12h, for example, the second insulation time may be 4h, 6h, 8h, 10h or 12h, etc.
[0056] By adjusting and controlling the parameters of the sintering treatment, such as the heating rate, sintering atmosphere, holding temperature and holding time, the protective film layer on the surface of the sintered foil can be removed cleanly, and at the same time, the surface of the sintered foil can be made flat and non-sticky, thereby ensuring the flatness and integrity of the surface of the sintered foil. Irregular multi-directional cracks can be generated on the surface and inside of the sintered foil to improve the bending resistance of the subsequently formed anode foil.
[0057] In the embodiment provided in the present disclosure, after step S5, the method further includes: boiling the sintered foil to form an intermediate anode foil; and chemically treating the intermediate anode foil to form an oxide layer on the intermediate anode foil to obtain a target anode foil.
[0058] The boiling treatment includes boiling the sintered foil in deionized water at 100°C for 5 to 15 minutes. The temperature of the deionized water may be 100°C in a strict sense, but due to temperature error, the temperature of the deionized water may also be within the range of 100°C±1°C, which may be considered as the temperature of the deionized water required during the boiling treatment. The boiling treatment time is 5 to 15 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes.
[0059] By adjusting and controlling the time and temperature of the water boiling treatment, a hydrated aluminum oxide layer of appropriate thickness can be formed on the surface of the sintered foil, which is beneficial to the formation of an oxide layer in the subsequent chemical treatment.
[0060] The formation treatment includes performing a formation treatment on the intermediate anode foil under the condition that the formation voltage is 200V to 700V. The formation voltage is 200V to 700V, for example, the formation voltage can be 200V, 300V, 400V, 500V, 600V or 700V, etc. The hydrated aluminum oxide layer can be converted into an oxide layer through the formation treatment, wherein the oxide layer is an aluminum oxide film layer.
[0061] By adjusting and controlling the formation voltage, anode foils with various rated withstand voltage requirements can be produced.
[0062] The disclosed embodiment also provides an aluminum electrolytic capacitor, which includes an anode foil prepared by the above method. The capacitor has good mechanical properties and good overall device performance.
[0063] The following is a further description of the method for preparing the anode foil provided by the present disclosure through specific examples: Comparative Example 1 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of the alumina ceramic powder is 0.5μm~10μm, and the mass fraction of the alumina ceramic powder in the solid aluminum-containing powder is 5%.
[0064] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0065] Step 3: The aluminum foil blank obtained in step 2 is passed through a roller with a diameter of 12 mm to produce cracks on the foil surface. The process is: first, the aluminum foil blank is passed through the roller at an angle of 40° between the length direction and the axis direction of the roller, and this is repeated 10 times; then, the aluminum foil blank is passed through the roller at an angle of 140° between the length direction and the axis direction of the roller, and this is repeated 10 times.
[0066] Step 4: Sinter the aluminum foil blank obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 1 hour; then, heating to 650°C in nitrogen at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0067] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0068] Comparative Example 2 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of the alumina ceramic powder is 0.5μm~10μm, and the mass fraction of the alumina ceramic powder in the solid aluminum-containing powder is 5%.
[0069] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0070] Step 3: The aluminum foil blank obtained in step 2 is passed through a roller (12 mm in diameter) with a ball (2 mm in diameter) on the circumferential surface that can rotate around its own ball center to process cracks on the foil surface. The process is: first, the aluminum foil blank is passed through the roller at an angle of 40° between the length direction and the axis direction of the roller, and this is repeated 10 times; then, the aluminum foil blank is passed through the roller at an angle of 140° between the length direction and the axis direction of the roller, and this is repeated 10 times.
[0071] Step 4: Sinter the aluminum foil blank obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 1 hour; then, heating to 650°C in nitrogen at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0072] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0073] Comparative Example 3 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of the alumina ceramic powder is 0.5μm~10μm, and the mass fraction of the alumina ceramic powder in the solid aluminum-containing powder is 5%.
[0074] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0075] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 30 μm.
[0076] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 1 hour; then, heating to 650°C in nitrogen at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0077] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0078] Example 1 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of the alumina ceramic powder is 0.5μm~10μm, and the mass fraction of the alumina ceramic powder in the solid aluminum-containing powder is 5%.
[0079] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0080] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 30 μm.
[0081] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 40° to the axis direction of the roller, and then the length direction of the aluminum foil with a protective film layer on the surface is rolled 10 times at 140° to the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a four-roll mill.
[0082] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 1 hour; then, heating to 650°C in nitrogen at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0083] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0084] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 1 had 152 longitudinal bending times, and 76 transverse bending times; the anode foil obtained in Control Example 2 had 174 longitudinal bending times, and 82 transverse bending times; the anode foil obtained in Control Example 3 had 3 longitudinal bending times, and 2 transverse bending times; the anode foil obtained in Example 1 had 185 longitudinal bending times, and 92 transverse bending times.
[0085] Compared with Comparative Examples 1 to 3, the anode foil obtained in Example 1 has the highest number of bending times. Figure 2 This is a light microscope image of the anode foil obtained by the preparation method provided in Comparative Example 1. Figure 3 This is a light microscope image of the anode foil obtained by the preparation method provided in Comparative Example 2. Figure 4 This is a light microscope image of the anode foil obtained by the preparation method provided in Example 1. Figure 2 and Figure 3 It can be seen that the anode foils obtained in Comparative Example 1 and Comparative Example 2 both have irregular multi-directional cracks, but the anode foil surfaces both have scratches and powder loss defects. Figure 4 It can be seen that the surface of the anode foil obtained in Example 1 has irregular multi-directional cracks, and the surface quality of the anode foil is good, without scratches and powder loss defects; the preparation method of Example 1 can obtain an anode foil with a smooth surface and good bending resistance.
[0086] Comparative Example 4 Step 1: Mix and stir the solvent (pinene alcohol and ethylene glycol), binder (ethyl cellulose), and additive (organic silicone defoamer) in a mass ratio of 50:50:3:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 3% and 7%, respectively.
[0087] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0088] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is screen printing; and the thickness of the protective film layer is 15 μm.
[0089] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 400°C in air at a heating rate of 10°C / min, and keeping the temperature for 4 hours; then, heating to 630°C in vacuum at a heating rate of 10°C / min, and keeping the temperature for 8 hours, and cooling with the furnace after the end of the heat preservation.
[0090] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0091] Example 2 Step 1: Mix and stir the solvent (pinene alcohol and ethylene glycol), binder (ethyl cellulose), and additive (organic silicone defoamer) in a mass ratio of 50:50:3:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 3% and 7%, respectively.
[0092] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0093] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is screen printing; and the thickness of the protective film layer is 15 μm.
[0094] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 30° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 150° to the axis direction of the roller; the roller pressure during the rolling process is 5 μm; the roller diameter is 300 mm; the rolling mill is a two-roll rolling mill.
[0095] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 400°C in air at a heating rate of 10°C / min, and keeping the temperature for 4 hours; then, heating to 630°C in vacuum at a heating rate of 10°C / min, and keeping the temperature for 8 hours, and then cooling with the furnace after the end of the heat preservation.
[0096] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0097] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 4 was bent once in the longitudinal direction and once in the transverse direction; the anode foil obtained in Example 2 was bent 169 times in the longitudinal direction and 98 times in the transverse direction.
[0098] Comparative Example 5 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), binder (polyvinyl butyral), additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of alumina, titanium dioxide and barium titanate is 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide and barium titanate in the solid aluminum-containing powder are 0.3%, 0.5% and 0.2%, respectively.
[0099] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0100] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry it to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 5 μm.
[0101] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 300°C in air at a heating rate of 20°C / min, and keeping the temperature for 8 hours; then, heating to 610°C in argon at a heating rate of 20°C / min, and keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0102] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0103] Example 3 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), (polyvinyl butyral), and additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the particle size of the aluminum powder is 0.5μm~5μm, the mass purity is 99.99%, the particle size of alumina, titanium dioxide and barium titanate is 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide and barium titanate in the solid aluminum-containing powder are 0.3%, 0.5% and 0.2%, respectively.
[0104] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0105] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry it to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 5 μm.
[0106] Step 4, rolling the aluminum foil blank with the protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with the protective film layer on the surface is rolled twice at 60° to the axis direction of the roller, and then the length direction of the aluminum foil blank with the protective film layer on the surface is rolled twice at 120° to the axis direction of the roller; the roller pressure during the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roller rolling mill.
[0107] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: first, heat from room temperature to 300°C in air at a heating rate of 20°C / min, and keep warm for 8 hours; then heat to 610°C in argon at a heating rate of 20°C / min, and keep warm for 12 hours, and then cool with the furnace after the insulation is completed.
[0108] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0109] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 5 had 2 longitudinal bends and 4 transverse bends; the anode foil obtained in Example 3 had 118 longitudinal bends and 61 transverse bends.
[0110] Comparative Example 6 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:25:5:3:5:1:1:4 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of aluminum oxide is 0.5μm~10μm, and the mass fraction of aluminum oxide in the solid aluminum-containing powder is 10%.
[0111] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0112] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 20 μm.
[0113] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 450°C in air at a heating rate of 1°C / min, and keeping the temperature for 1 hour; then, heating to 650°C in nitrogen at a heating rate of 1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0114] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0115] Example 4 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:25:5:3:5:1:1:4 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, alumina ceramic powder) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of aluminum oxide is 0.5μm~10μm, and the mass fraction of aluminum oxide in the solid aluminum-containing powder is 10%.
[0116] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180 degrees, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0117] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 20 μm.
[0118] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 40° in the length direction and the axis direction of the roller, and then the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 160° in the length direction and the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a four-roll mill.
[0119] Step 5, sintering the rolled aluminum foil obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly heating from room temperature to 450°C in air at a heating rate of 1°C / min, and keeping the temperature for 1 hour; then heating to 650°C in nitrogen at a heating rate of 1°C / min, and keeping the temperature for 4 hours, and cooling with the furnace after the end of the heat preservation.
[0120] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0121] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 6 had 1 longitudinal bending time and 2 transverse bending times; the anode foil obtained in Example 4 had 166 longitudinal bending times and 65 transverse bending times.
[0122] Comparative Example 7 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and ethylene glycol), binder (polyvinyl butyral), additive (organic silicone defoamer and triethanolamine dispersant) in a mass ratio of 40:20:40:3:0.5:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 4% and 1%, respectively.
[0123] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0124] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0125] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 350°C in air at a heating rate of 5°C / min, and keeping the temperature for 6 hours; then, heating to 640°C in vacuum at a heating rate of 10°C / min, and keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0126] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0127] Example 5 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and ethylene glycol), binder (polyvinyl butyral), additive (organic silicone defoamer and triethanolamine dispersant) in a mass ratio of 40:20:40:3:0.5:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 4% and 1%, respectively.
[0128] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0129] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0130] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 20° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 140° to the axis direction of the roller; the roller pressure during the rolling process is 15 μm; the roller diameter is 300 mm; the rolling mill is a three-roll mill.
[0131] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: first, heat from room temperature to 350°C in air at a heating rate of 5°C / min, and keep warm for 6 hours; then heat to 640°C in vacuum at a heating rate of 10°C / min, and keep warm for 12 hours, and then cool with the furnace after the insulation is completed.
[0132] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0133] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 7 was bent 2 times in the longitudinal direction and 2 times in the transverse direction; the anode foil obtained in Example 5 was bent 175 times in the longitudinal direction and 75 times in the transverse direction.
[0134] Comparative Example 8 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, propylene glycol), binder (ethyl cellulose), and additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 50:30:20:5:0.5:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are all 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 0.6%, 0.2%, and 0.2%, respectively.
[0135] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0136] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 10 μm.
[0137] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 300°C in air at a heating rate of 10°C / min, and keeping the temperature for 8 hours; then, heating to 620°C in argon at a heating rate of 5°C / min, and keeping the temperature for 6 hours, and then cooling with the furnace after the end of the heat preservation.
[0138] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0139] Example 6 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, propylene glycol), binder (ethyl cellulose), and additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 50:30:20:5:0.5:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are all 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 0.6%, 0.2%, and 0.2%, respectively.
[0140] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20 μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60 μm.
[0141] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 10 μm.
[0142] Step 4, rolling the aluminum foil blank with the protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with the protective film layer on the surface is rolled twice at 70° to the axis direction of the roller, and then the length direction of the aluminum foil blank with the protective film layer on the surface is rolled twice at 110° to the axis direction of the roller; the roller pressure during the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roll rolling mill.
[0143] Step 5, sintering the rolled aluminum foil obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly heating from room temperature to 300°C in air at a heating rate of 10°C / min, and keeping the temperature for 8 hours; then heating to 620°C in argon at a heating rate of 5°C / min, and keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0144] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0145] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 8 had 1 longitudinal bending time and 3 transverse bending times; the anode foil obtained in Example 6 had 136 longitudinal bending times and 72 transverse bending times.
[0146] Comparative Example 9 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol and propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, dispersant triethanolamine and silane coupling agent) in a mass ratio of 50:40:10:3:7:1:1:2:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of alumina is 0.5μm~10μm, and the mass fraction of alumina in the solid aluminum-containing powder is 10%.
[0147] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0148] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 30 μm.
[0149] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 15°C / min, and keeping the temperature for 4 hours; then, heating to 640°C in nitrogen at a heating rate of 3°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0150] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0151] Example 7 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol and propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, dispersant triethanolamine and silane coupling agent) in a mass ratio of 50:40:10:3:7:1:1:2:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of alumina is 0.5μm~10μm, and the mass fraction of alumina in the solid aluminum-containing powder is 10%.
[0152] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0153] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is blade coating; and the thickness of the protective film layer is 30 μm.
[0154] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled twice at 60° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled twice at 110° to the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a four-roll mill.
[0155] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 15°C / min, and keeping the temperature for 4 hours; then, heating to 640°C in nitrogen at a heating rate of 3°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0156] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0157] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 9 had 12 longitudinal bends and 15 transverse bends; the anode foil obtained in Example 7 had 109 longitudinal bends and 70 transverse bends.
[0158] Comparative Example 10 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose) and additive (silicone defoamer and silane coupling agent) in a mass ratio of 30:30:30:10:8:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 3.5% and 1.5%, respectively.
[0159] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0160] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is screen printing; and the thickness of the protective film layer is 20 μm.
[0161] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 450°C in air at a heating rate of 3°C / min, and keeping the temperature for 6 hours; then, heating to 630°C in vacuum at a heating rate of 15°C / min, and keeping the temperature for 10 hours, and then cooling with the furnace after the end of the heat preservation.
[0162] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0163] Example 8 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose) and additive (silicone defoamer and silane coupling agent) in a mass ratio of 30:30:30:10:8:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are both 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 3.5% and 1.5%, respectively.
[0164] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60 μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50 μm.
[0165] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is screen printing; and the thickness of the protective film layer is 20 μm.
[0166] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 15 times at 20° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 15 times at 135° to the axis direction of the roller; the roller pressure during the rolling process is 5 μm; the roller diameter is 300 mm; the rolling mill is a two-roll rolling mill.
[0167] Step 5, sintering the rolled aluminum foil obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly heating from room temperature to 450°C in air at a heating rate of 3°C / min, and keeping the temperature for 6 hours; then heating to 630°C in vacuum at a heating rate of 15°C / min, keeping the temperature for 10 hours, and cooling with the furnace after the end of the heat preservation.
[0168] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0169] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 10 had 11 longitudinal bends and 14 transverse bends; the anode foil obtained in Example 8 had 161 longitudinal bends and 106 transverse bends.
[0170] Comparative Example 11 Step 1: Mix and stir the solvent (butyl acetate, propylene glycol and glycerol), binder (polyvinyl butyral), and additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 90:5:5:5:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide and barium titanate are 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide and barium titanate in the solid aluminum-containing powder are 0.2%, 0.3% and 0.5%, respectively.
[0171] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0172] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is blade coating; and the thickness of the protective film layer is 25 μm.
[0173] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 20°C / min, and keeping the temperature for 8 hours; then, heating to 620°C in nitrogen at a heating rate of 20°C / min, and keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0174] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0175] Example 9 Step 1: Mix and stir the solvent (butyl acetate, propylene glycol and glycerol), binder polyvinyl butyral, and additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 90:5:5:5:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide and barium titanate) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide and barium titanate are 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide and barium titanate in the solid aluminum-containing powder are 0.2%, 0.3% and 0.5%, respectively.
[0176] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0177] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is blade coating; and the thickness of the protective film layer is 25 μm.
[0178] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 45° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 160° to the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 600 mm; the rolling mill is a two-roll rolling mill.
[0179] Step 5, sintering the rolled aluminum foil obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly heating from room temperature to 500°C in air at a heating rate of 20°C / min, and keeping the temperature for 8 hours; then heating to 620°C in nitrogen at a heating rate of 20°C / min, and keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0180] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0181] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 11 had 13 longitudinal bends and 12 transverse bends; the anode foil obtained in Example 9 had 97 longitudinal bends and 98 transverse bends.
[0182] Comparative Example 12 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicon defoamer and dispersant triethanolamine) in a mass ratio of 20:40:36:2:2:9:1:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of aluminum oxide is 0.5μm~10μm, and the mass fraction of aluminum oxide in the solid aluminum-containing powder is 5%.
[0183] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0184] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the thickness of the protective film layer is 15 μm.
[0185] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 400°C in air at a heating rate of 10°C / min, and keeping the temperature for 4 hours; then, heating to 610°C in vacuum at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0186] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0187] Example 10 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicon defoamer and dispersant triethanolamine) in a mass ratio of 20:40:36:2:2:9:1:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of aluminum oxide is 0.5μm~10μm, and the mass fraction of aluminum oxide in the solid aluminum-containing powder is 5%.
[0188] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0189] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the thickness of the protective film layer is 15 μm.
[0190] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 45° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 135° to the axis direction of the roller; the roller pressure during the rolling process is 5 μm; the roller diameter is 200 mm; the rolling mill is a three-roll mill.
[0191] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 400°C in air at a heating rate of 10°C / min, and keeping the temperature for 4 hours; then, heating to 610°C in vacuum at a heating rate of 0.1°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0192] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0193] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 12 was bent once in the longitudinal direction and once in the transverse direction; the anode foil obtained in Example 10 was bent 194 times in the longitudinal direction and 163 times in the transverse direction.
[0194] Comparative Example 13 Step 1: Mix and stir the solvent (pinene alcohol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, dispersant triethanolamine and silane coupling agent) in a mass ratio of 95:5:8:2:2:2:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 0.7% and 0.3%, respectively.
[0195] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0196] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0197] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 350°C in air at a heating rate of 20°C / min, and keeping the temperature for 4 hours; then, heating to 620°C in argon at a heating rate of 3°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0198] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0199] Embodiment 11 Step 1: Mix and stir the solvent (pinene alcohol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, dispersant triethanolamine and silane coupling agent) in a mass ratio of 95:5:8:2:2:2:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:150 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are 0.7% and 0.3%, respectively.
[0200] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0201] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0202] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 20° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 20 times at 110° to the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a four-roll mill.
[0203] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 350°C in air at a heating rate of 20°C / min, and keeping the temperature for 4 hours; then, heating to 620°C in argon at a heating rate of 3°C / min, and keeping the temperature for 4 hours, and then cooling with the furnace after the end of the heat preservation.
[0204] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0205] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 13 had 2 longitudinal bends and 3 transverse bends; the anode foil obtained in Example 11 had 169 longitudinal bends and 81 transverse bends.
[0206] Comparative Example 14 Step 1: Mix and stir the solvent (butyl acetate and ethylene glycol), binder (ethyl cellulose and polyvinyl butyral), and additive (organic silicone defoamer and silane coupling agent) in a mass ratio of 50:50:6:2:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:200 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 3%, 1%, and 1%, respectively.
[0207] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0208] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is blade coating; and the thickness of the protective film layer is 25 μm.
[0209] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 300°C in air at a heating rate of 2°C / min, and keeping the temperature for 2 hours; then, heating to 640°C in vacuum at a heating rate of 5°C / min, and keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0210] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0211] Example 12 Step 1: Mix and stir the solvent (butyl acetate and ethylene glycol), binder (ethyl cellulose and polyvinyl butyral), and additive (organic silicone defoamer and silane coupling agent) in a mass ratio of 50:50:6:2:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:200 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 3%, 1%, and 1%, respectively.
[0212] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0213] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is blade coating; and the thickness of the protective film layer is 25 μm.
[0214] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 2 times at 70° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 160° to the axis direction of the roller; the roller pressure during the rolling process is 15 μm; the roller diameter is 100 mm; the rolling mill is a four-roll mill.
[0215] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: first, heat from room temperature to 300°C in air at a heating rate of 2°C / min, and keep warm for 2 hours; then heat to 640°C in vacuum at a heating rate of 5°C / min, and keep warm for 12 hours, and then cool with the furnace after the insulation is completed.
[0216] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0217] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 14 had 5 longitudinal bends and 3 transverse bends; the anode foil obtained in Example 12 had 129 longitudinal bends and 67 transverse bends.
[0218] Comparative Example 15 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicone defoamer and acrylic leveling agent) in a mass ratio of 20:30:45:5:5:5:1:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of alumina is 0.5μm~10μm, and the mass fraction of alumina in the solid aluminum-containing powder is 1%.
[0219] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 55μm.
[0220] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the thickness of the protective film layer is 30 μm.
[0221] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 450°C in air at a heating rate of 5°C / min, and keeping the temperature for 4 hours; then heating to 620°C in nitrogen at a heating rate of 0.1°C / min, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0222] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0223] Example 13 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicone defoamer and acrylic leveling agent) in a mass ratio of 20:30:45:5:5:5:1:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina) in a mass ratio of 100:80 to obtain a protective film layer; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle size of alumina is 0.5μm~10μm, and the mass fraction of alumina in the solid aluminum-containing powder is 1%.
[0224] Step 2: Apply the protective film layer obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180 degrees, apply the protective film layer on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30 μm, and the thickness of the protective film layer coated on the upper and lower surfaces after drying is 55 μm.
[0225] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the thickness of the protective film layer is 30 μm.
[0226] Step 4, rolling the aluminum foil blank with the protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with the protective film layer on the surface is rolled 20 times at 60° to the axis direction of the roller, and then the length direction of the aluminum foil blank with the protective film layer on the surface is rolled 20 times at 160° to the axis direction of the roller; the roller pressure during the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roller rolling mill.
[0227] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 450°C in air at a heating rate of 5°C / min, and keeping the temperature for 4 hours; then, heating to 620°C in nitrogen at a heating rate of 0.1°C / min, and keeping the temperature for 12 hours, and then cooling with the furnace after the end of the heat preservation.
[0228] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0229] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 15 was bent 2 times in the longitudinal direction and 4 times in the transverse direction; the anode foil obtained in Example 13 was bent 158 times in the longitudinal direction and 109 times in the transverse direction.
[0230] Comparative Example 16 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), the binder polyvinyl butyral, and the additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are both 1%.
[0231] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0232] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0233] Step 4: Sinter the aluminum foil blank with a protective film layer on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 2 hours; then, heating to 630°C in argon at a heating rate of 5°C / min, and keeping the temperature for 12 hours, and then cooling with the furnace after the end of the heat preservation.
[0234] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0235] Embodiment 14 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), the binder polyvinyl butyral, and the additives (silicone defoamer and acrylic leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina and titanium dioxide) in a mass ratio of 100:250 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina and titanium dioxide are 0.5μm~10μm, and the mass fractions of alumina and titanium dioxide in the solid aluminum-containing powder are both 1%.
[0236] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 60μm.
[0237] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of polyethylene glycol; the coating method is blade coating; and the thickness of the protective film layer is 15 μm.
[0238] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the aluminum foil blank with a protective film layer on the surface is rolled 10 times at an angle of 20° between the length direction and the axis direction of the roller, and then the aluminum foil blank with a protective film layer on the surface is rolled 10 times at an angle of 160° between the length direction and the axis direction of the roller; the roller pressure during the rolling process is 5 μm; the roller diameter is 500 mm; and the rolling mill is a two-roll rolling mill.
[0239] Step 5, sintering the rolled aluminum foil obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly heating from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keeping the temperature for 2 hours; then heating to 630°C in argon at a heating rate of 5°C / min, and keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0240] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0241] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 16 had 7 longitudinal bends and 12 transverse bends; the anode foil obtained in Example 14 had 145 longitudinal bends and 70 transverse bends.
[0242] Comparative Example 17 Step 1: Mix and stir the solvent (terpineol, diethylene glycol butyl ether acetate, ethylene glycol), binder (ethyl cellulose), and additive (silicone defoamer) in a mass ratio of 50:10:40:6:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are all 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 2.5%, 1%, and 1.5%, respectively.
[0243] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0244] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 10 μm.
[0245] Step 4: Sinter the aluminum foil with the protective film on the surface obtained in step 3. The sintering is carried out in a bell-type furnace, and the sintering process is: firstly, heating from room temperature to 300°C at a heating rate of 1°C / min in air, and keeping the temperature for 1 hour; then, heating to 650°C at a heating rate of 20°C / min in nitrogen, and keeping the temperature for 6 hours, and then cooling with the furnace after the end of the heat preservation.
[0246] Step 5: The sintered foil obtained in step 4 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0247] Embodiment 15 Step 1: Mix and stir the solvent (terpineol, diethylene glycol butyl ether acetate, ethylene glycol), binder (ethyl cellulose), and additive (silicone defoamer) in a mass ratio of 50:10:40:6:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, ceramic powder alumina, titanium dioxide, and barium titanate) in a mass ratio of 100:80 to obtain an aluminum-containing slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, the particle sizes of alumina, titanium dioxide, and barium titanate are all 0.5μm~10μm, and the mass fractions of alumina, titanium dioxide, and barium titanate in the solid aluminum-containing powder are 2.5%, 1%, and 1.5%, respectively.
[0248] Step 2: Apply the aluminum-containing slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the aluminum-containing slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum-containing slurry applied on the upper and lower surfaces after drying is 50μm.
[0249] Step 3: Coat the upper and lower surfaces of the aluminum foil blank obtained in step 2 with a thin film solution, and dry the solution to obtain a protective film layer. The thin film solution is an aqueous solution of hydroxyethyl cellulose, hydroxypropyl methyl cellulose and polyvinyl alcohol; the coating method is screen printing; and the thickness of the protective film layer is 10 μm.
[0250] Step 4, rolling the aluminum foil blank with a protective film layer on the surface obtained in step 3. The rolling method is oblique rolling, and the rolling process is: first, the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 40° to the axis direction of the roller, and then the length direction of the aluminum foil blank with a protective film layer on the surface is rolled 10 times at 110° to the axis direction of the roller; the roller pressure during the rolling process is 10 μm; the roller diameter is 400 mm; the rolling mill is a two-roll rolling mill.
[0251] Step 5: Sinter the rolled aluminum foil blank obtained in step 4. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: first, heat from room temperature to 300°C in air at a heating rate of 1°C / min, and keep warm for 1 hour; then heat to 650°C in nitrogen at a heating rate of 20°C / min, and keep warm for 6 hours, and then cool with the furnace after the insulation is completed.
[0252] Step 6: The sintered foil obtained in step 5 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0253] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 17 had 13 longitudinal bends and 8 transverse bends; the anode foil obtained in Example 15 had 167 longitudinal bends and 56 transverse bends.
[0254] The bending performance test results of the anode foils prepared in Comparative Example 1 to Comparative Example 17 and Examples 1 to Example 15 are shown in Table 1: Table 1
[0255] It can be seen from Table 1 that the anode foil prepared in Comparative Example 1 and treated by an inclined roller has 152 longitudinal bending times and 76 transverse bending times; the anode foil prepared in Comparative Example 2 and treated by an inclined roller with a ball rotatable around its own spherical center has 174 longitudinal bending times and 82 transverse bending times; the anode foil prepared in Example 1 and treated by oblique rolling by a rolling mill has 185 longitudinal bending times and 92 transverse bending times; under the condition of the same number of treatments, the anode foil prepared in Example 1 has a higher number of bending times than the anode foils prepared in Comparative Example 1 and Comparative Example 2.
[0256] In addition, the anode foils prepared in Control Example 3 to Control Example 17 without rolling treatment have poor transverse and longitudinal bending resistance, and the number of bending times is less than 20 times; the anode foils prepared in Example 1 to Example 15 using a rolling mill for oblique rolling have a transverse bending number of more than 50 times and a longitudinal bending number of more than 90 times. By comparing Control Example 3 to Control Example 17 with Example 1 to Example 15, it can be seen that under the same test conditions, the bending times of the anode foils prepared in Example 1 to Example 15 are increased by more than 400% compared with the anode foils prepared in Control Example 3 to Control Example 17, which greatly improves the transverse and longitudinal bending resistance of the anode foil and meets the requirements of mechanical processing. Therefore, the method for preparing the anode foil provided in the present disclosure can improve the bending resistance of the anode foil, thereby improving the overall performance of the device.
[0257] It should be noted that, although the steps of the method for preparing the anode foil in the present disclosure are described in a specific order in the accompanying drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0258] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
Claims
1. A method for preparing an anode foil, characterized in that: include: Step S1: preparing an aluminum-containing slurry, wherein the aluminum-containing slurry comprises a mixed solution and a solid aluminum-containing powder, wherein the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder comprises aluminum powder and ceramic powder; Step S2: providing an aluminum foil substrate, coating the aluminum-containing slurry on the surface of the aluminum foil substrate, and performing a drying process to form an aluminum foil blank; Step S3: coating a thin film solution on the surface of the aluminum foil blank, and performing a drying process to form a protective film layer on the surface of the aluminum foil blank; Step S4: using a rolling mill to perform a rolling process on the aluminum foil blank having the protective film layer in a skew rolling manner to obtain an initial anode foil; Step S5: sintering the initial anode foil to remove the protective film layer to form a sintered foil.
2. The method for preparing an anode foil according to claim 1, characterized in that: The rolling mill is one of a two-roll rolling mill, a three-roll rolling mill or a four-roll rolling mill, the rolling mill has a rolling roller pressure of 5 μm to 15 μm, and a rolling roller diameter of 65 mm to 600 mm. In step S4, the aluminum foil blank having the protective film layer is rolled by the rolling mill in a skew rolling manner to obtain an initial anode foil. The method includes: The aluminum foil blank having the protective film layer is subjected to a first rolling process, wherein the first rolling process is to repeatedly roll the aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 20° to 70° with the length direction of the aluminum foil blank; The aluminum foil blank with the protective film layer is then subjected to a second rolling treatment, wherein the second rolling treatment is to repeatedly roll the aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 110° to 160° with the length direction of the aluminum foil blank.
3. The method for preparing an anode foil according to claim 1, characterized in that: The film solution is an aqueous solution prepared by one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; in step S3, the film solution is coated on the surface of the aluminum foil blank, and the method comprises: The aluminum foil blank is coated with the thin film solution on both sides by using a doctor blade coating or screen printing method; the thickness of the protective film layer on each side of the aluminum foil blank is the same, and the thickness of the protective film layer on each side of the aluminum foil blank is 5μm~30μm.
4. The method for preparing an anode foil according to claim 1, characterized in that: The mass fraction of the ceramic powder to the solid aluminum-containing powder is 1% to 10%; the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80 to 250).
5. The method for preparing an anode foil according to claim 4, characterized in that: The ceramic powder is one or more of aluminum oxide, titanium dioxide, barium titanate, and strontium titanate; and the particle size of the ceramic powder is 0.5 μm to 10 μm.
6. The method for preparing an anode foil according to claim 1, characterized in that: The mass ratio of the solvent, the binder and the additive in the mixed solution is 100:(3-10):(0.5-10); The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or both of terpineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol; The binder is one or two of ethyl cellulose and polyvinyl butyral; The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent.
7. The method for preparing an anode foil according to claim 1, characterized in that: The thickness of the aluminum foil substrate is 20 μm to 60 μm, and the aluminum foil substrate has an upper surface and a lower surface that are arranged opposite to each other. In step S2, the aluminum foil blank is formed. The method includes: The aluminum foil substrate is double-sided coated with the aluminum-containing slurry to form aluminum slurry film layers with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; Under the condition of a drying temperature of 90° C. to 200° C., the aluminum foil substrate having the aluminum paste film layer is dried, and the thickness of the aluminum paste film layer after drying is 50 μm to 60 μm.
8. The method for preparing an anode foil according to claim 1, characterized in that: In step S5, the sintering process includes: In an air atmosphere, heating the initial anode foil from room temperature to 300° C. to 500° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 1 h to 8 h; In a nitrogen, argon or vacuum atmosphere, the initial anode foil is continuously heated to 610° C. to 650° C. at a heating rate of 0.1° C. / min to 20° C. / min, and kept at this temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
9. The method for preparing an anode foil according to claim 1, characterized in that: After step S5, the method further comprises: The sintered foil is subjected to a water boiling treatment to form an intermediate anode foil, wherein the water boiling treatment comprises boiling the sintered foil in deionized water at 100° C. for 5 to 15 minutes; The intermediate anode foil is subjected to a chemical formation treatment to form an oxide layer on the intermediate anode foil to obtain a target anode foil, wherein a chemical formation voltage of the chemical formation treatment is 200V to 700V.
10. An aluminum electrolytic capacitor, characterized in that: The invention relates to an anode foil prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Aluminum foil for aluminum electrolytic capacitor electrode and method for manufacturing the same
CN102122576A
A novel three-dimensional porous aluminum electrode foil and a preparation method thereof
CN109036852A
Method for preparing anode foil of aluminum electrolytic capacitor by means of cold rolling machine
CN113458143A
Porous electrode foil and preparation process thereof
CN114523112A
Preparation method of sintered anode foil added with nano high-dielectric fibers
CN115692027A
Cited By
Preparation method of anode foil and aluminum electrolytic capacitor
CN122474496A